SEJARAH ISLAM DI PAKISTANDAN IDE-IDE PEMBAHARUAN MUHAMMAD ALI JINNAH - Sera Yuliantini; Mauizatul Hasanah; Agri Arisa; M. Dahlan. M; Syamzan Syukur (Adisam Publisher, 2025)
The history of Islam in Pakistan is a long story that began with the arrival of Islam on the Indian subcontinent through Islamic expansion in the 7th century. Islamic influence grew rapidly over time, making this region a center of Islamic culture with strong influences from Muslim kingdoms such as the Delhi Sultanate and the Mughal Empire. The formation of Pakistan in 1947 was an important point in the history of Islam in the region, where Pakistan was established as a state for Muslims based on Islamic religious and cultural principles. Muhammad Ali Jinnah, the founder and first leader of Pakistan, played a major role in the formation of this country. His ideas about religious freedom, minority rights, and the need for a modern and progressive Islamic state became an important basis in his political struggle. Jinnah emphasized the importance of inter-religious tolerance and unity among Muslims, while continuing to support democratic principles and state laws based on Islamic values. The reforms introduced by Jinnah aimed to ensure that Pakistan's ethnic and religious diversity could coexist peacefully within a state framework that respected individual freedom and social justice. Thus, the history of Islam in Pakistan and Jinnah's reformist ideas played a central role in the country's development, illustrating how Islamic values and modern politics can go hand in hand in building an independent and inclusive state.